2013
DOI: 10.1590/0103-6440201302164
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Fatigue Resistance of Rotary NiTi Instruments after Simulated Clinical Use in Curved Root Canals

Abstract: The aim of this study was to assess cyclic fatigue resistance in rotary nickel-titanium instruments after simulated clinical use in curved root canals (40-degree, 5-mm radius curve). Thirty-six RaCe rotary NiTi files, size #5, taper 0.04, were divided into 3 groups: Groups A, B and C with one, three and five cycles of use, respectively. Time to failure was recorded with a stopwatch in seconds and subsequently converted to number of cycles to fracture. The data were analyzed statistically by ANOVA and Tukey's t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
0
20
1
1
Order By: Relevance
“…Cutting edges with alternating matter can avoid the screwing effect and working with low torque. This instrument can create centered canal shapes with enough clean and shaped canals (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Cutting edges with alternating matter can avoid the screwing effect and working with low torque. This instrument can create centered canal shapes with enough clean and shaped canals (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Continuous cycles of traction and compression in curved canals are reported to increase the cyclic fatigue and fracture of endodontic files (Melo et al 2002, Zelada et al 2002, Pessoa et al 2013.…”
Section: Kinematics Of Movement and Instrument Fracturementioning
confidence: 99%
“…The relationship between cyclic fatigue and the dynamics of the forces exerted by NiTi rotary files on root canals during experimental canal preparation has been poorly discussed. Previous reports have reported that dynamic pecking motion tests are the Kinematics and cyclic fatigue of NiTi instruments Ferreira et al most suitable for cyclic fatigue investigations when using rotary NiTi files, as static tests are not able to reproduce the real conditions faced in clinical practice such as automated instrumentation systems (Yared et al 2000, Pessoa et al 2013).…”
Section: Kinematics Of Movement and Instrument Fracturementioning
confidence: 99%
“…The results of mean deformation scores that recorded in the present study are supported by the results of deformation percentage, where TFA instruments used with reciprocating motion produced the lowest deformation percentage (10%) followed by TFA instruments used with adaptive motion (30%) while the highest deformation percentage was recorded in TFA instruments used with continuous rotation motion (40%). The highest mean deformation scores and deformation percentage recorded with the continuous rotation motion could be explained by increased instrument experiences in tension/compression during rotation at the point of greatest curvature, which increase the cyclic fatigue and separation of endodontic files (29,30) . Moreover, it has been reported that, the continuous rotation motion is leading cause of NiTi instrument failure, with deformation, metal fatigue and subsequent breakage being potential problems associated with the use of 360 rotary instruments in curved canals (31) .…”
Section: Discussionmentioning
confidence: 99%